2015
DOI: 10.18268/bsgm2015v67n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Calpionellid biostratigraphy, U-Pb geochronology and microfacies of the Upper Jurassic-Lower Cretaceous Pimienta Formation (Tamazunchale, San Luis Potosí, central-eastern Mexico)

Abstract: Detailed sampling of a stratigraphic section corresponding to the La Pimienta Formation in the state of San Luis Potosí allows the determination of the upper Tithonian Crassicollaria Zone (Remanei, Brevis and Colomi Subzones). The presence of Praetintinnopsella andrusovi Borza and chitinoidellids in the Crassicollaria Zone, was interpreted as the result of sedimentary reworking as due to fact that these taxa have not been reported in such a high stratigraphic position. Nonetheless additional work is needed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Zircons from ash interbeds in southern Tibet, confined to the Berriasian ammonites and assemblages of calcareous nannofossils, yielded SIMS U–Pb ages ranging from 140.0 ± 1.3 to 141.8 ± 1.2 Ma (Liu et al., 2013). The U–Pb age of zircons from the Pimienta Formation (central‐eastern Mexico) bentonite layer overlying the late Tithonian Crassicollaria Zone and underlying the early Berriasian Calpionella Zone was determined as 139.1 ± 2 Ma (Lopez‐Martínez et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Zircons from ash interbeds in southern Tibet, confined to the Berriasian ammonites and assemblages of calcareous nannofossils, yielded SIMS U–Pb ages ranging from 140.0 ± 1.3 to 141.8 ± 1.2 Ma (Liu et al., 2013). The U–Pb age of zircons from the Pimienta Formation (central‐eastern Mexico) bentonite layer overlying the late Tithonian Crassicollaria Zone and underlying the early Berriasian Calpionella Zone was determined as 139.1 ± 2 Ma (Lopez‐Martínez et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…mahoney et al as can be seen, assigning a numerical age for the J-K boundary can be difficult. over the last twenty-five years, dating has relied on different approaches and on some repeated assumptions, which have yielded a large range of ages: from 135 to 145 Ma Bralower et al, 1990;Gradstein et al, 1995;Mahoney et al, 2005;liu et al, 2013;Vennari et al, 2014;López-Martínez et al, 2015a). Currently ( 2019 The model (ogg et al, 2012) is based on a spline-fitting model that predicts the ages of stage boundaries from the Early Cretaceous (aptian) to the Late Jurassic (oxfordian).…”
Section: Radio-isotopic Age Constraints On the Jurassic/cretaceous Bomentioning
confidence: 99%
“…However, pioneering research on calpionellids by Воnet (1956) was followed by that of Trejo (1960Trejo ( , 1975Trejo ( , 1980Trejo ( ) and adatte et al (1994. More recently, a crop of results from López-Martínez et al (2013b, 2015a, from apulco, Tamazunchale and San José de Iturbide have revealed a full complement of biozones across the Tithonian-Berriasian boundary, with calcareous dinocysts, as well as accessory data on radiometric dates, and, most recently, calcareous nannofossils (Lena et al, 2019). This widespread evidence refutes uninformed criticisms of the work of Bonet and Trejo, and provides unequivocal correlations with Tethys and the Crassicollaria and Calpionella zones of other regions.…”
Section: The Americas (Excluding Arctic Canada)mentioning
confidence: 99%
“…To this may be added the often overlapping and even wider distributions of calcareous nannofossils and dinocysts (e.g., Atlantic, North Africa, Canada, South America, Japan, Antarctic, California, Tibet, Australian shelf, Arctic). The widespread application of 'Tethyan' calpionellids in Mexico, supplanting purely regional ammonite biozonations, (López-Martínez et al, 2013b, 2015a and the Andes (there with nannofossils in parallel, and the first recorded magnetostratigraphy) (Riccardi, 2015;López-Martínez et al, 2017;Iglesia Llanos et al, 2017) are, in this J/K context, the greatest achievements in the Americas in recent years. They mean that, for the first time, a 'Tethyan' pattern of fossil markers (primary and supporting) approaches becoming a global pattern.…”
Section: Markers Defining the Boundary At Tré Marouamentioning
confidence: 99%